An empirical examination of the dynamics of varietal turnover in Indian wheat - Krishna, Vijesh V.; Spielman, David J.; Veettil, Prakashan C.; Ghimire, Subash (International Food Policy Research Institute, 2014)
This paper addresses the challenge of increasing the rate of varietal turnover to prevent depreciation of improved cultivars over time. It examines the supply of and demand for improved cultivars of wheat in India to illustrate this challenge in a unique manner, combining national-level data on breeder seed production with primary data on cultivar adoption. The analyses show that the rate of varietal turnover for wheat has slowed in India from an average of 9-10 years a decade ago to 13-14 years in 2010. By focusing on a sample of farmers and villages in Haryana, where seed and information networks are relatively well developed, the study finds that wheat farmers still prefer cultivars that were released 9-10 years ago.